2018
DOI: 10.1007/s00464-018-6587-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical trainee impact on bariatric surgery safety

Abstract: Background Roux-en-Y-gastric bypass (RYGB) and sleeve gastrectomy (SG) are commonly performed bariatric procedures that are associated with a significant learning curve. The effect of surgeon experience on perioperative outcomes and safety is established, but the effect of trainee participation remains unclear. The purpose of this study was to assess the impact of trainees on early perioperative safety of bariatric surgery. Methods Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…There are several limitations of this study. While the MBSAQIP data set is the most comprehensive bariatric database available, it is devoid of information that may identify surgeon training level and experience [12,[49][50][51]. Details of patient income level, insurance status, and geographic location are also absent from the dataset, and may provide additional information regarding socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations of this study. While the MBSAQIP data set is the most comprehensive bariatric database available, it is devoid of information that may identify surgeon training level and experience [12,[49][50][51]. Details of patient income level, insurance status, and geographic location are also absent from the dataset, and may provide additional information regarding socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The Sx values were summed sequentially and then plotted as a graph using the equation: CUSUM = ΣSx. [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 13 16 ] Moreover, participation of trainees resulted in higher rates of anastomosis leakage, readmissions, re-interventions, and complications. [ 14 ] In contrast, Abu-Ghanem et al [ 17 ] found that assistant's experience levels had no influence on operative outcomes. The effects of bedside assistants on surgical outcomes for thyroid surgery have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many surgical procedures have been developed, however the principles that govern the standard procedures today follow two fundamental ideas, limiting gastric capacity (restrictive) and altering the absorption of the small intestine (malabsorptive) [ 5 ]. It is almost a rule that higher complexity procedures are associated with greater weight loss and better resolutions of most of the comorbidities such as diabetes and hypertension [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%